CRISPR/Cas12a Technology Combined With RPA for Rapid and Portable SFTSV Detection - Huang, Mengqian; Liu, Sihua; Xu, Yanan; Li, Aqian; Wu, Wei; Liang, Mifang; Niu, Guoyu; Wang, Zhiyun; Wang, Tao (Frontiers in Microbiology, 2022)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is a new tick-borne pathogen that can cause severe hemorrhagic fever. Fever with thrombocytopenia syndrome caused by SFTSV is a new infectious disease that has posed a great threat to public health. Therefore, a fast, sensitive, low-cost, and field-deployable detection method for diagnosing SFTSV is essential for virus surveillance and control. In this study, we developed a rapid, highly sensitive, instrument-flexible SFTSV detection method that utilizes recombinase polymerase amplification and the CRISPR/Cas12a system. We found that three copies of the L gene from the SFTSV genome per reaction were enough to ensure stable detection within 40 min. The assay clearly showed no cross-reactivity with other RNA viruses. Additionally, our method demonstrated 100% agreement with Q-PCR detection results for SFTSV in 46 clinical samples. We simplified the requirements for on-site detection instruments by combining the CRISPR/Cas12a tool and immunochromatographic strips to create a system that can reliably detect one copy/μl sample of the L gene, which showed extremely high sensitivity and specificity for detecting the virus. Taken together, these findings indicate that the new SFTSV detection method is a powerful and effective tool for on-site detection, which can contribute to diagnosing SFTSV quickly and sensitively.